KARAKTERISTIK HABITUS DAN LINGKUNGAN POHON SARANG SEMUT RANGRANG (Oecophylla smaragdina) DI BANDAR LAMPUNG - Dewi Ariska; Suratman Umar; Nismah Nukmal; M. Kanedi (Jurnal Ilmiah Biologi Eksperimen dan Keanekaragaman Hayati (J-BEKH), 2019)
The weaver ant (Oecophylla smaragdina) is a eusocial insect, whose colonic life is highly dependent on the existence of trees. The existence of the weaver ant in natural habitat is now reduced due to the destruction of habitats caused by humans. To preserve the existence of weaver ant in nature needs to be studied bioecology as the purpose of this research is to know the characteristics of habitus and environment of weaver ants nest in Bandar Lampung. The research was conducted in June-October 2017 at the location of yard and plantation, using 50% sample from the sample population, from 20 districts in Bandar Lampung, 10 sub-districts were used as randomly selected research sites. The results showed as many as 15 types of plants used weaver ant for nesting. The most widely planted species of weaver ant is Mangifera sp. with characteristics of slippery surface habitus, sympodial branching, tree height of 3.9 to 11.5 m and an average canopy of> 65%, more nests found in yards (76%) far from urban areas, the percentage of the dominant nest toward the east , which is 41.8% of the total number of 86 nests.